2021
DOI: 10.1186/s12883-021-02252-2
|View full text |Cite
|
Sign up to set email alerts
|

Initial in-hospital heart rate is associated with three-month functional outcomes after acute ischemic stroke

Abstract: Background Increased heart rate (HR) has been associated with stroke risk and outcomes. Material and methods We analyzed 1,420 patients from a hospital-based stroke registry with acute ischemic stroke (AIS). Mean initial in-hospital HR and the coefficient of variation of HR (HR-CV) were derived from the values recorded during the first 3 days of hospitalization. The study outcome was the 3-month functional outcome. Odds ratios (ORs) with 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Higher heart rate at rest was associated with poorer functional status in the elderly and predicted subsequent functional decline independently of cardiovascular risk factors ( 46 ). Higher initial in-hospital heart rate also predicted poorer stroke outcomes ( 47 ). The potential influence of these additional predictors on the development of SAP may warrant further research.…”
Section: Discussionmentioning
confidence: 99%
“…Higher heart rate at rest was associated with poorer functional status in the elderly and predicted subsequent functional decline independently of cardiovascular risk factors ( 46 ). Higher initial in-hospital heart rate also predicted poorer stroke outcomes ( 47 ). The potential influence of these additional predictors on the development of SAP may warrant further research.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cardiac complications are frequently found in patients with acute stroke. Relevant studies mainly focused on ischemic stroke and subarachnoid hemorrhage, but few studies are on ICH [ 3 , 4 ]. A study has shown that cardiac complications may occur in 1% to 4% of patients with ICH [ 5 ].…”
Section: Introductionmentioning
confidence: 99%